Social factors affecting job satisfaction and their relation to the level of health services provided to society - Al-Mansour, Reem Mansour Ahmed (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed to the following: Identifying the job satisfaction and its relation with health services provided to society.  Identifying the factors affecting on job satisfaction and its relation with level of health services provided to society. Identifying the impacts of development of job satisfaction level and its relation with level of health services. Identifying the appropriate methods to increase the job satisfaction level and quality of health services. To achieve these objectives, the researcher used the analytical descriptive method in order to achieve aims of the study. She has chosen a random Population of 261 employees of Ministry of Health and used the questionnaire with closed form to collect its data. The study found out some results as: The (252) employees, of the total staff of the Ministry of Health (Population) are Saudis; while (9) employees, of the total staff of the Ministry of Health; are non-Saudis.  The Ministry of Health staff (the Population) are satisfied that there are certain to raise the level of job satisfaction appropriate mechanisms, and the quality of health services. The Ministry of Health staff (the Population) are satisfied that there are some effects of improving the level of job satisfaction, and its relationship to the level of health services provided to the community. The researcher recommended some of the recommendations and most important: Providing human potential, physical, and technical service to the sick, and raise the level of job satisfaction, and the level of health services provided to the community. Working on removing the causes of lack of job satisfaction as many work pressures, such as: marginalization, long working hours and lack of recognition of the social, psychological and administrative disciplines, and lack of integration of services provided to patients. Working on staff participation in planning and decision-making process; as it affects the level of job satisfaction to have.
Keywords: social factors; job satisfaction; health services; society